Effects of artificially induced bilateral internal rotation gait on gait kinematics and kinetics - Thielen, Mirjam; Waible, Dorothea; Krautwurst, Britta; Wolf, Sebastian Immanuel; Dreher, Thomas (Gait & posture, 2022)
Background - Bilateral internal rotation gait is a common gait abnormality in children with bilateral cerebral palsy, but still not fully understood. - Research question - The aim of this clinical study was to analyze the effects of artificially induced bilateral internal rotation gait on kinematics and kinetics. Our hypothesis was, that the internal rotation gait defined as increased dynamic internal hip rotation itself causes significant alterations in gait kinematics and kinetics. - Methods - 30 typically developing children with a mean age of 12 (SD 3) years (range 8 - 16) performed three-dimensional gait analysis in two different conditions: with unaffected gait and with artificially induced bilateral internal rotation gait with two rotation bandages worn in order to internally rotate the hips. Kinematic and kinetic changes between these two conditions were calculated and compared using a mixed linear model with “gait condition” as fixed effect and both “limb” and “patient” as random effects. - Results - The rotation bandages induced a significant increase in internal hip rotation and foot progression angle towards internal without affecting pelvic rotation. The peak hip internal rotator moment during loading response and the peak hip external rotator moment during the first half of stance phase increased significantly and the peak hip internal rotator moment during the second half of stance phase decreased significantly. Anterior pelvic tilt, hip flexion, knee flexion and ankle dorsiflexion increased significantly. The first peak of the frontal hip moment decreased, and the second increased significantly. The second peak of the frontal knee moment decreased significantly, while the first didn’t change significantly. - Significance - The data suggest, that the bilaterally increased dynamic internal hip rotation itself has a relevant impact on frontal hip moments. The increased anterior pelvic tilt, hip and knee flexion may be either induced by the pull of the rotation bandage or a secondary gait deviation.
Gesehen am 01.07.2022
Available online 4 May 2022